The impact of building form on overheating control: a case study of Larch House. (1st November 2020) - Lavafpour, Yahya; Sharples, Steve; Gething, Bill
Abstract : Amid recent concern about overheating in Passivhaus, this study investigates geometrical implication of façade design to alleviate overheating in new build energy-efficient homes in the UK. The study proposes self-shading façade design as a less conventional approach to passively protecting the house from the excessive solar gain in summer. The findings show that implementing an optimum angle slanted wall can moderate indoor temperature variations between day and night in summer and could potentially act as an effective shading device. The suggested tilted façade is compared alongside other conventional approaches, such as overhangs and reduced WWR, to compare their relative effectiveness in reducing overheating risk.